The role of neuropeptides in cutaneous wound healing: a focus on mechanisms and neuropeptide-derived treatments - Xing, Liwei; Chen, Bing; Qin, Yuliang; Li, Xinyao; Zhou, Sitong; Yuan, Kai; Zhao, Rong; Qin, Dongdong (Frontiers in Bioengineering and Biotechnology, 2024)
An extensive network of cutaneous nerves, neuropeptides, and specific receptors richly innervates the skin and influences a variety of physiological and pathological processes. The sensory and autonomic nerve fibers secrete a variety of neuropeptides that are essential to the different phases of wound healing. In addition to initiating a neurogenic inflammatory response in the early stages of healing, neuropeptides also control wound healing by influencing immune cells, repair cells, and the growth factor network. However, the precise mechanism by which they accomplish these roles in the context of cutaneous wound healing is still unknown. Investigating the mechanisms of action of neuropeptides in wound healing and potential therapeutic applications is therefore urgently necessary. The present review discusses the process of wound healing, types of neuropeptides, potential mechanisms underlying the role of neuropeptides in cutaneous wound healing, as well as some neuropeptide-derived treatment strategies, such as hydrogels, new dressings, electro stimulation, and skin-derived precursors. Future in-depth mechanistic studies of neuropeptides in cutaneous wound healing may provide opportunities to develop therapeutic technologies that harness the roles of neuropeptides in the wound healing process.